Morphology and phylogeny reveal two new species and a new geographical record of Agaricus sect. Rubricosi (Agaricales) from West Bengal, India - Entaj Tarafder; Samantha C. Karunarathna; Arun Kumar Dutta; Abdallah M. Elgorban; Feng-Hua Tian; Krishnendu Acharya (Scientific Reports)
Abstract Two new species (Agaricus tumlingensis, and A. philippei) and one new record (A. kunmingensis) belong to the sect. Rubricosi of the subg. Pseudochitonia, are described from India based on morphological and molecular sequence (nrITS and LSU rDNA) data. Agaricus tumlingensis is distinguished by its medium to large-sized basidiomata, brown to dark brown squamulose pileus, ellipsoid to elongate basidiospores with a range value of 5.5–7.5 × 3.5–4.0 μm, and cheilocystidia measuring 15–34 × 9–17 μm. Agaricus philippei has a dark brown appressed squamulose pileus, ellipsoid basidiospores with a range value of 4.5–5.1 × 2.5–3.0 μm, and cheilocystidia measuring 11–21 × 7–14 μm. Detailed morphological descriptions, illustrations, field photographs of the collected basidiomata, comparisons with morphologically similar species, and phylogenetic analysis results based on the nrITS and nrLSU sequence data are provided.